Improvisasi Manajemen Pembelajaran Untuk Efektivitas Pencapaian Tujuan Pembelajaran - Ahmad Faiz Mahbubi Addaraini; Nuril Mufidah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2022)
During this pandemic, many lecturers improvise in learning management because teaching no longer runs with a standard system but runs more flexibly based on conditions in the field. Included in the learning of management courses for class E MPBA UIN Malang, which is the goal to be described in this study. This research includes descriptive qualitative research, data collection techniques using interviews and observations, while data analysis in this study uses spiral analysis techniques where the authors reinterpret the data found repeatedly and adjust the results to the research objectives. The results of this study indicate; 1) the learning planning stage in this course is declared effective because it does not burden students and helps them complete research articles more quickly, 2) the organizing or class management stage is declared effective because it can maintain optimal learning conditions online, 3) the implementation stage is declared less effective because the use of WhatsApp groups reduces students' enthusiasm in working on articles, and 4) the evaluation stage, is declared effective because it meets the principles in the theory of evaluation of learning outcomes which consist of the overall principle, the principle of continuity, and the principle of objectivity.